The role of green finance in reshaping end-use energy consumption: insights from regional evidence in China - Deng, Mingzheng; Lu, Xiangyi; Tong, Ruibin; Xue, Yan; Shi, Shuaihang; Guo, Rui (Frontiers in Environmental Science, 2025)
IntroductionGreen finance plays a pivotal role in the transition to a low-carbon economy by influencing energy consumption patterns. Despite growing interest in this area, the relationship between green finance and the optimization of end-use energy consumption remains underexplored, particularly in the context of regional disparities.MethodsThis study investigates the impact of green finance on end-use energy consumption structure across 30 provinces in China from 2014 to 2021. A system Generalized Method of Moments (GMM) model and a panel threshold model are employed to analyze the relationship, incorporating nonlinearities and regional heterogeneities.ResultsThe findings indicate that green finance significantly reduces reliance on high-carbon energy sources and fosters cleaner energy consumption, particularly in provinces with advanced green financial systems. The effects are nonlinear, becoming evident only after green finance surpasses a certain threshold. Stronger impacts are observed in eastern regions due to mature financial infrastructures, whereas central and western regions experience comparatively weaker outcomes.DiscussionContrary to expectations, mediating factors such as industrial structure, energy efficiency, and green innovation have limited explanatory power for the observed impacts. These results highlight the need for tailored green financial policies and enhanced regional support mechanisms to accelerate sustainable energy transitions. This research underscores the transformative potential of green finance in energy governance and its contribution to achieving sustainable development goals.